Global Minimum Tax: Implications and Recommendations for Multinational Corporations - Dilaga, Tirta Prasetya; Daryatno, Andreas Bambang (Journal Research of Social Science, Economics, and Management, 2025)
The implementation of the global minimum tax under the OECD's Pillar Two framework marks a pivotal shift in international taxation, designed to curb profit shifting by multinational corporations (MNCs) to low-tax jurisdictions. This research aims to analyze the mechanism of this policy and its implications for MNCs, with a specific focus on Indonesia's adoption through Minister of Finance Regulation (PMK) No. 136 of 2024. Using a qualitative literature study method, this study examines the operational aspects of the Global Anti-Base Erosion (GloBE) Rules, including the Income Inclusion Rule (IIR), Undertaxed Payment Rule (UTPR), and Domestic Minimum Top-up Tax (DMTT). The findings indicate that the global minimum tax fundamentally alters the international tax competition landscape, rendering aggressive tax planning strategies less effective and significantly increasing compliance complexity for MNCs. Key implications include the need for MNCs to reassess their global tax strategies, optimize the use of Safe Harbour provisions, and strengthen tax governance frameworks. The study concludes with strategic recommendations for MNCs to navigate this new tax environment, emphasizing holistic impact assessments and the realignment of transfer pricing policies.